CHANGING FORMS OF GUILLAIN-BARRé SYNDROME IN NEURO-ICU. Issue 10 (9th September 2014) - Howard, Robin; Taylor, Chris; Playford, Diane; Kullmann, Dimitri; Hirsch, Nicholas
Abstract : Up to 25% of patients with Guillain-Barré syndrome (GBS) require intensive care, tracheal intubation and mechanical ventilation. The patterns of referral for specialised Neuro-ICU care have changed with the introduction of intravenous immunoglobulin. We reviewed all GBS admissions to the Batten Unit, Queen Square over a 20 year period and compared the cohort admitted during the first 10 years to the second. 112 patients were admitted for ventilation. All were treated with either intravenous immunoglobulin or plasma exchange. 56 patients were admitted during the first 10 year period and a further 56 patients in the most recent ten-year period. The incidence of patients admitted with axonal GBS increased from 26%, in the first 10 years, to 46% in the most recent 10 years and this was associated with a significant increase in the duration of ventilation, intensive care stay and the severity of disability at the time of discharge. However, mortality fell from 12.5% to 5.3%. These results indicate the proportion of patients with the most severe axonal form of GBS referred to our specialist unit is increasing, whilst this is associated with a longer period of ICU stay, the mortality has fallen.